PERSEPSI MASYARAKAT PADA KETERBUKAAN INFOMASI (E-GOVERNMENT) KOTA BANDA ACEH MENUJU SMART CITY - Alhadi Sutama; Fikriah Fikriah (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract Smart city is the latest solution in urban areas. One of the pillars of this smart city is information disclosure which is the basis of service for the city community. Openness of information is an important measure so that government transparency with the community can work. This study aims to look at the perceptions of the people of Banda Aceh in the openness of e-government information towards smart cities. The research data used primary data with 100 respondents. The method of research analysis uses descriptive and testing relationships with crosstab chi-square. The results of the study show that city profile indicators and information access reports are the main measure for people to go to smart cities. However, there are obstacles in terms of accuracy and information updates, which are still very low. The implementation of e-government public services shows that access to information can be reached by the people of Banda Aceh. The results of statistical tests found 4 indicators that have a significant relationship with Banda Aceh's e-government, namely city profiles, financial reports, information access reports, and implementation of public service e-government.Keywords: Smart City, Information Openness, E-government, Crosstab, Chi-Square